The Influence of Entrepreneurial Orientation and Strategy on the Performance of Micro, Small, and Medium Enterprises in Batununggal District, Bandung City - Syadza Zahrah Sausan; Mukaram (Ebiz Prima Nusa, 2024)
This study analyzes the impact of entrepreneurial orientation and strategy on the performance of small and medium enterprises ( MSMEs) in Batununggal District, Bandung City. Entrepreneurial orientation is measured through autonomy, competitive aggressiveness, innovation, and proactiveness, while entrepreneurial strategy is assessed through innovation, proactiveness, and opportunity seeking. MSMEs performance is evaluated based on operational efficiency, growth performance, product and service quality, and customer satisfaction. Using a descriptive quantitative approach, the study involved 149 respondents from a population of 670 MSMEs, selected through the Slovin formula and purposive sampling. Data was collected through structured questionnaires using a Likert scale, validated through pilot testing. The respondent profile shows that the majority are in the culinary field, with business durations ranging from new to well-established. Most respondents earn more than two million rupiah per month. Demographic data indicates that most respondents have established businesses with relatively good income, reflecting a representative sample. Results show